2016
DOI: 10.1186/s40064-016-2081-0
|View full text |Cite
|
Sign up to set email alerts
|

Surface disinfection procedure and in vitro regeneration of grapevine (Vitis vinifera L.) axillary buds

Abstract: Establishment of an efficient explants surface disinfection protocol is essential for in vitro cell and tissue culture as well as germplasm conservation, such as the case of Grapevine (Vitis spp.) culture. In this research, different procedures for disinfection and regeneration of field-grown grapevine cv. ‘Flame seedless’ axillary buds were evaluated. The buds were disinfected using either NaOCl or allyl, benzyl, phenyl and 2-phenylethyl isothiocyanates. Two different media for shooting and four media for roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 43 publications
(48 reference statements)
0
11
0
3
Order By: Relevance
“…A etapa de introdução de material vegetal em condições in vitro é complexa devido aos altos percentuais de contaminação pela proliferação de bactérias e fungos, difíceis de serem eliminados (Alfenas et al 2009;Xavier et al 2013). O uso de substâncias desinfestantes como etanol, hipoclorito de sódio e de cálcio, peróxido de hidrogênio, ácido clorídrico, ácido sulfúrico são relatados como eficientes na descontaminação de diferentes explantes de espécies vegetais (Silva et al 2015b;Lazo-Javalera et al 2016;Silva et al 2016;Müller et al 2017).…”
Section: Discussionunclassified
“…A etapa de introdução de material vegetal em condições in vitro é complexa devido aos altos percentuais de contaminação pela proliferação de bactérias e fungos, difíceis de serem eliminados (Alfenas et al 2009;Xavier et al 2013). O uso de substâncias desinfestantes como etanol, hipoclorito de sódio e de cálcio, peróxido de hidrogênio, ácido clorídrico, ácido sulfúrico são relatados como eficientes na descontaminação de diferentes explantes de espécies vegetais (Silva et al 2015b;Lazo-Javalera et al 2016;Silva et al 2016;Müller et al 2017).…”
Section: Discussionunclassified
“…Sterility of explants is probably the most difficult challenge with field grown explants due to their high contamination levels (Lazo-Javalera et al 2016, Laimer da Câmara Machado et al 1991. The establishment of in vitro cultures from woody plant material collected from Cornus species growing in the open field since centuries is reported to be a difficult task, owing to explant losses by fungal contaminations (Edson et al 1994) and to detrimental conditions such as vitrification or chlorosis (Ilczuk and Jacygrad 2016).…”
Section: Culture Initiation and Long-term Conservation Of Wildtype Accessionsmentioning
confidence: 99%
“…An alternative method for plants with these kinds of problems is an in vitro plant propagation method, which has been applied successfully to other systems (Hassan and Zayed, 2018). Other studies have demonstrated the merits of this approach, such as high propagation efficiencies produced through the application of plant growth regulators (PGRs) and avoidance of seasonal and space barriers for propagation work, compared to conventional propagation methods in many economically important crops (Lazo-Javalera et al, 2016;Mozafan et al, 2017;Toma, 2018). However, several researchers have indicated that the efficiency of in vitro propagation for Vitis spp.…”
Section: Effects Of Plant Growth Regulators For Root Induction and Acclimatizationmentioning
confidence: 99%